Peran Audit Syariah dalam Meningkatkan Akuntabilitas pada Organisasi Pengelola Zakat : The Role of Sharia Audit in Increasing Accountability in Zakat Management Organizations - Umiyati, Umiyati; muhibudin, muhibudin; Habibullah, Habibullah; Rini, Rini (Direktorat Jenderal Bimbingan Masyarakat Islam, 2023)
Sharia audit is one way to maintain and ensure the integrity of zakat management financial institutions in carrying out sharia principles. Sharia audit can provide assurance to stakeholders and is urgently needed to respond to developments in the Islamic finance industry. The purpose of this research is to describe the role of Islamic audit in increasing accountability in Zakat Management Organizations. This study uses a qualitative method with a descriptive approach. The validity of the data is done by technical triangulation. The results of the study show that based on the Regulation of the Minister of Religion (PMA) Number 606 of 2020, Sharia Audit must be carried out in a comprehensive, accurate, transparent and accountable manner, therefore there is a need for Sharia Audit guidelines for reports on the Implementation of the Management of Zakat, Infaq, Charity and Religious Social other. Broadly speaking, there are many weaknesses in terms of governance, dual control, transparency & administration in the management of Zakat Management Organizations, so that optimization of the implementation of sharia audits by the Ministry of Religion can be expanded to cover Zakat Management Organizations audited in order to increase the accountability of Zakat Management Organizations. Keywords: Sharia Audit, Accountability, Zakat Management Organization